The Recreational Correlations of Urbanisation Processes in Hungary - Antal Aubert; Veronika Hegedüs (Journal for Geography, 2006)
The recreational correlations of urbanisation processes in HungaryThe settlement network of Hungary has reached a development phase by now where not only concentration processes but also disurbanisation phenomena can be seen. This has led to the birth or urban spaces of different types, in which spaces the functions satisfying the recreational needs of the local society are becoming more and more important. Recreation, in addition to “tourism” in the classic sense of the word, is a process meeting the demands of the local population and affecting the image and the identity of the settlement, which is available for most of the people up to the level of their leisure time. (Recreation as a possibility to spend leisure time can be interpreted in a wider context that also involves tourism, but in this paper the narrower interpretation is considered as valid.)Beyond the former, mainly touristic division of the space, the paper places the recreation-related phenomena and spaces within the system of urbanisation processes; also, the by the examination of the demand and supply side it justifies the importance of the research. Following the introduction of the theoretical background, the paper focuses – through a case study – on the development of the settlement network around Kaposvár and the recreation possibilities and spaces of the respective area.